2001
DOI: 10.1007/s100960100549
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Microevolution in a Clinical Case of Recurrent Cryptococcus neoformans Meningoencephalitis

Abstract: The aim of this study was to examine three serial isolates of Cryptococcus neoformans from a patient with AIDS for genotypical and phenotypical characteristics. The isolates were obtained during a first episode of cryptococcosis (simultaneous sampling of blood and cerebrospinal fluid) and after a relapse 3 years later (sampling of cerebrospinal fluid). Pulsed-field gel electrophoresis and random amplification of polymorphic DNA revealed that the blood isolate 1525 (first episode) was different from the two cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 51 publications
1
39
0
1
Order By: Relevance
“…Studies of BF often use Candida strains passaged in laboratories (3,31) that have been adapted to culture media, and thus they may not be representative of BF in clinical strains. Microevolution of fungal pathogens occurs in vitro and in vivo and can affect major virulence factors (5,6,13,14,36). In the present study we determined that BF among clinical Candida strains varied significantly and ranged from high to low.…”
Section: Discussionmentioning
confidence: 67%
“…Studies of BF often use Candida strains passaged in laboratories (3,31) that have been adapted to culture media, and thus they may not be representative of BF in clinical strains. Microevolution of fungal pathogens occurs in vitro and in vivo and can affect major virulence factors (5,6,13,14,36). In the present study we determined that BF among clinical Candida strains varied significantly and ranged from high to low.…”
Section: Discussionmentioning
confidence: 67%
“…In this case, IL-10 upregulation resulted in downregulation of excessive inflammation (a drop in the cell count in the CSF), which then permitted proper clearance (14). Several studies have shown that most clinical strains have the ability to vary their phenotypes with respect to colony morphology, polysaccharide structure, and cellular morphology (4,11,21,56), and different colony phenotypes can be observed in primary CSF isolates even before the start of therapy (18). Our data indicate that changes in phenotype translate into different host inflammatory responses and ultimately outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these patients often exhibit for a prolonged time high fungal burdens that promote the selection of switch variants with enhanced virulence which could ultimately result in treatment failure. Several studies have now shown that cryptococcal isolates can exhibit heterogeneous phenotypes with respect to colony morphology, polysaccharide structure, and cellular morphology (2,8,21,50). These studies suggest that most clinical strains have the ability to vary their phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Several observations support the concept that microevolution of C. neoformans occurs during the course of mammalian infection. First, prolonged in vitro and in vivo passage of C. neoformans isolates can result in phenotypic changes associated with differences in virulence, as demonstrated in murine infection models (2,6,8,11,17). Second, serial isolates from chronically infected patients can exhibit differences in virulence (18).…”
mentioning
confidence: 99%